A model volcanic fissure with adjustable geometry and wall temperature - R. P. Cole; J. D. L. White; R. J. M. Baxter; M. H. Bowman; T. Dürig; M. Fleming; B. Pooley; J. Ruz-Ginouves; M. T. Gudmundsson; S. J. Cronin; G. S. Leonard; G. A. Valentine (Bulletin of Volcanology, 2023)
Fissure eruptions initiate with magma ascending and spreading through cracks in the ground that can extend for kilometres at the surface. Eruptions eventually localise to form one or a few persistent conduits and ultimately an array of discrete cones or craters. We built a new experimental apparatus to investigate the influences of fissure shape and wall-rock temperature on localisation within a volcanic fissure, and the thermal feedbacks associated with variability of these parameters. Our artificial fissure, or “Artfish,” has a slot geometry with adjustable shape and wall temperature. We can simulate both starting variability in fissure geometry and wall temperature, as well as changes in these parameters during an experiment to replicate, for example, blockage by wall-rock collapse, widening by wall-rock erosion, and warming by adjacent intrusions. We use polyethylene glycol (PEG 600) for our analogue fluid. A variable-speed pump allows for a range of fluid injection and ascent rates. Initial tests showcase the capabilities of the model and the types of data that may be acquired. Additional key features achieved include a stable and planar injection system, fluid recycling, and the use of particle tracers for monitoring flow patterns and velocities. The thermal evolution of the fluid-wall interface is quantitatively measured with thermal sensors, and the change in state of the PEG provides a clear visual indication of flow behaviour and solidification progress recorded on video. The potential experiments that can be conducted with this highly versatile model are numerous and will be used to gain a better understanding of the thermal controls on flow localisation and conduit development. This will assist hazard modellers to assess controls on eruption evolution and potentially to forecast sites where an initial fissure eruption may focus.